BY CALCULATING THE STEADY PRESSURE FILTRATION TO DRAINAGE IN LOOSE SOILS - and (Municipal economy of cities. Series: «Economy science», 2013)
The formulas for calculating the unique filtration resistance due to the reorientation of the skeleton non-cohesive soil particles under the influence of pipe drainage. The evaluation of the significance of this effect for the action of self-flowing wells perfect.